Desenvolvimento de uma garra robótica utilizando molas de liga com memória de forma como atuador - Souza, Josué da Silva (2018)
The scientific and technological advance provided a revolution in several areas, among them is the rehabilitation engineering, which has benefited among other forms with the manufacture of more functional and light prostheses. However, the number of prosthesis rejection by users to upper limbs is high. The main reasons for this low acceptance are directly related to the lack of anthropomorphism, high weight, existence of noise, low agility and high acquisition and maintenance costs. In this context, this work is presented the development of a robotic claw using shape memory alloy springs (LMF). The mechanical structure of the robotic claw consists of two fingers, the indicator with three degrees of freedom and a static thumb in opposable position to perform the clamping movement. The prototype was designed in a virtual CAD environment and made of ABS polymer with anthropomorphic characteristics. For actuation of the claw was designed an actuator with four shape memory alloy springs arranged in parallel physically. The actuator had to undergo a thermomechanical characterization process, to better understand the characteristics such as: current, temperature, displacement, force, deformation and time. To monitor the angles formed in the movement of the prototype a camera was used.